A grounded theory study of the implementation of spatial data infrastructure in Zimbabwe; the professional identity perspective - Mahiya, Vincent (Midlands State University, 2017)
Needs for spatial data are increasing due to the different uses it can be put to. Due to the progress in digitalization, the volumes of data in various fields are accumulating quickly at an unprecedented speed. Different types of spatial resources come from different units but they may be integrated effectively through SDI development so that users can easily obtain and apply the shared resources. Spatial Data Infrastructures (SDIs) enable access, sharing and propagation of spatial data needed for complex decision-making processes of the future. Many countries are introducing SDIs. Zimbabwe has not been an exception. The initial efforts were not fruitful. Therefore, there is need to find out how the multiple professional identities in Zimbabwe. Professional identity, can be defined as one‘s professional self-concept based on attributes, beliefs, values, motives, and experiences. This research sought to come up with a theory about the implementation of SDIs in Zimbabwe based on the multifaceted survey professional identities. There has been a lot of research on SDIs but there is little research on using Professional Identity as a lens. The research methodology used was the Grounded Theory research. The author collected data during fieldwork in Zimbabwe at different institutions in private and government institutions using interviews guided by a questionnaire. The data was analysed according to the dictates of this methodology and subsequently a theory was produced. From the research, it was noted that it is not merely a case of whether or not the frameworks produced before on the implementation of SDIs were suited for a country like Zimbabwe. However, there were others factors that needed to be considered for the SDI initiative to be fruitful. Factors include the pride among professionals as this determines how a person carries out their duties. This pride led to the issue of dominance of one professional identity over others, consequently leaving other professionals feeling inferior. Technology has a great role to play as well because the key role players in the implementation should be aware of their duties as well as how to execute them with the available technology as well as being able to change according to the demands and technological changes involved. All the professionals are aware of SDIs and their importance. However, for the successful implementation, there is need for legislature that recognizes and protects other professional identities within the Surveying profession. This is vital because for the successful implementation of SDIs in Zimbabwe, all stakeholders should play their part. However, this can only be achieved if the Survey professionals feel important thereby leading to them being zealous to see the initiative through. This guarantees the initiative‘s success.